Juridical Analysis of The Implications of Security Council Referral in Regards to The Obligation of Non-State Parties to Cooperate With the International Criminal Court - Teuku Muktasim; Mahfud Mahfud (Jurnal Ilmiah Mahasiswa Bidang Hukum Pidana, 2019)
This research aims to see whether the Security Council Referrals actually imposed the obligation to cooperate with the International Criminal Court to Sudan and Libya, considering their status as Non-state Parties to the Rome Statute and to describe the obstacles faced by the International Criminal Court in securing the fulfillment of its cooperation requests to Sudan and Libya. This research is conducted in normative or legal doctrinal approach and relies on the data from primary sources and secondary sources. The primary sources included are; the Rome Statute, the UN Charter, case law, and UN bodies decisions. This research also include law commentaries, journals and textbooks, as secondary sources. This research argues that while The Resolutions S/RES/1593 (2005) and S/RES/1570 (2011) does not specify the obligations imposed towards Sudan and Libya respectively, it is right to conclude that since the resolutions does not provide an alternative cooperation regime, the cooperation regime contained in Part 9 of the Rome Statute applies. Despite this, the Court does not have the power to enforce obligation Sudan and Libya. It can only issue judicial findings of non-compliance, and leaving the Security Council and international community to pressure non-compliant States. It is recommended that in future referrals, the Security Council would use a more precise language to prevent misinterpretation. Meanwhile, appropriate international response is necessary to tackle the current noncompliance issue of Sudan and Libya.